THE POSITION OF THE KINGDOM OF SAUDI ARABIA AND JORDAN ON THE EISENHOWER DOCTRINE IN 1957 - Al-Wais, Ismail Mohammed Hassan (Journal of Learning on History and Social Sciences, 2025)
Objective: This investigation focuses on the stand taken by the Kingdom of Saudi Arabia and the Hashemite Kingdom of Jordan, vis a vis the Eisenhower Doctrine made public by the United States in 1957 as part of its containment policy toward Soviet penetration in the Middle East. Method: The doctrine took shape after the Suez crisis and the ascendance of Arab nationalism as championed by Egyptian leader Gamal Abdel Nasser, prompting Washington to offer its allies in the region direct military assistance to compensate for the rising power in the Arab world. Results: Saudi Arabia adopted the doctrine with a degree of caution, officially embracing it but did not directly get involved or use it as an excuse for intervention in Arab countries' affairs. This was in light of its struggle to ensure the independence of Arab decision-making atoning between regional relations and international dimensions, in addition to fears of the doctrine as a tool for establishing US hegemony. Jordan’s attitude was based on fluctuation, marked by heavy internal and external pressures. At first, King Hussein refused to embrace the doctrine to avoid popular and nationalist backlash, but with economic crisis and external security threats, eventually he could not escape aid offered by the US based on the doctrine with a marginal room for maneuvering. Novelty: The article asserts that these responses by each country to the Eisenhower Doctrine indicate the manner in which elements of the Middle East's political realities were entangled at that time; interests in the observance of national sovereignty, in obtaining Western aid, and in responding to rapidly occurring political transformation in the region.